Digital soil mapping of Jethuwal, Punjab, India for climate-smart fertilization in field crops - BHATT, RAJAN; DWIVEDI, DHAVAL K.; ARORA, SANJAY; SINGH, BIKRAMJIT (Journal of Soil and Water Conservation, 2026)
To support climate-smart fertilization, the current attempt intends to create digital soil maps (DSMs) of Jethuwal village of Verka block, Amritsar, Punjab. DSM for different soil physico-chemical and macro nutrients were prepared using ArcGIS software by first selecting 30 boundary points and thereafter 132 soil sampling points (0-15 cm) with coordinates by using GPS-60 (GARMIN) to address these geographical soil differences. Collected soil samples were analyzed in the soil and water testing lab of Krishi Vigyan Kendra, Amritsar, for electrical conductivity, soil pH, soil organic carbon, available phosphorus, and potassium, respectively. First, an outer boundary map was produced, and DSMs were prepared by superimposing different values for different nutrients. Analysis revealed that the village had a sandy loam texture, a pH range of 6.89 to 6.85, an EC range of 0.31 to 0.69 m-mhos cm-1, SOC reported to be lower in 87.2% of samples, available P ranging from 13.0 to 16.8 mg kg-1, and finally available K with a range of 100 to 188 mg kg-1. Underground water also reported to be of good quality. For SOC, the samples’ Parker Nutrient Index (PNI) values were reported to be lower for soil organic carbon (1.11) while higher for available P and K (3.00). The correlation table reveals only weak associations among soil parameters, with pH slightly influencing available P (0.24) and EC weakly linked to SOC, P, and K. Therefore, DSM- based crop fertilization is required for practicing judicious, climate-smart, and plant-need-based chemical fertilization in Jethuwal, which on one side reduces overall costs of cultivation while on the other improves the soil health.